Measurement of the W+ W- production cross section and search for anomalous WWγ and WWZ couplings in pp collisions at square root(s)=1.96 TeV. - Aaltonen, T; Adelman, J; Alvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Apresyan, A; Arisawa, T; Artikov, A; et al. (2010)
This Letter describes the current most precise measurement of the W boson pair production cross section and most sensitive test of anomalous WWγ and WWZ couplings in pp collisions at a center-of-mass energy of 1.96 TeV. The WW candidates are reconstructed from decays containing two charged leptons and two neutrinos. Using data collected by the CDF II detector from 3.6  fb(-1) of integrated luminosity, a total of 654 candidate events are observed with an expected background of 320±47 events. The measured cross section is σ(pp→W+ W- +X)=12.1±0.9(stat)-1.4+1.6(syst)  pb, which is in good agreement with the standard model prediction. The same data sample is used to place constraints on anomalous WWγ and WWZ couplings.